PF.64 Complicated Sequelae of Parvovirus Affected Pregnancies. (26th April 2013) - Flood, K; Burke, N; Muellers, S; Malone, FD
Abstract : During the recent epidemic of Parvovirus infection, three complicated pregnancies were managed in the Rotunda Hospital. The fetuses were significantly affected in all three cases, presenting with ultrasonographic findings consistent with severe anaemia; all required intra-uterine fetal transfusions. Case 1: The first case involved a 30 year old multip who presented at 20 weeks with severe fetal hydrops and a history of Parvovirus exposure. Severe fetal thrombocytopenia was noted at the time of cordocentesis. Repeated intrauterine transfusions were required however fetal cardiac function deteriorated further which resulted in fetal demise. Case 2: The second cases involved a 32 year old multip with confirmed Parvovirus infection who was referred with severe fetal hydrops. Severe thrombocytopenia was again noted however a successful fetal transfusion was performed. Unfortunately the mother subsequently developed Ballantyne (Mirror) syndrome which resolved with expectant management. Case 3: The final case involved a 28 year old multip with a dichorionic twin pair both of which were severely anaemic with similar haematocrit levels at cordocentesis. Both twins received the same treatment course however different outcomes were encountered. This case series demonstrates the various complications that add further challenging features to the management of pregnancies affected by Parvovirus infection.